Assessing Customer Satisfaction at XYZ Bank: A SERVQUAL-AHP Approach to Improve Service Quality - Kurniawan, Alvin; Putro, Utomo Sarjono (Integrasi Sains Media, 2025)
Competition within the banking sector is currently fierce. Competition compels banks to deliver enhanced service quality. Every Bank is vying to deliver superior service to clients. Service quality is a crucial prerequisite for enhancing and sustaining client happiness. Content consumers will offer endorsements, whilst discontented consumers will express grievances. In its 2024 annual report, XYZ Bank reported that, in conjunction with increased transaction volumes, it received a total of 22,369 complaints in 2024, representing a 13% rise of 2,526 complaints compared to the same period in 2023. This article will help companies assess their current level of customer satisfaction and identify the characteristics of service quality that require improvement. This study employed a hybrid methodology that combined SERVQUAL and AHP to derive a customer satisfaction index (CSI). Utilizing purposive sampling, 400 clients of XYZ Bank from Bandung City and six customer service professionals employed by XYZ Bank were chosen as participants. The CSI calculation results indicate that service quality achieves a moderate satisfaction level of 54.80%, with the most significant deficiency in the reliability component, succeeded by assurance, responsiveness, tangibles, and empathy dimensions. Based on Importance-Performance Analysis (IPA) and weighted gap scores, several indicators from the Reliability dimension require immediate corrective action, while indicators from the Responsiveness and Assurance dimensions need to continue improving to maintain quality. Indicators that require immediate corrective action, along with suggestions for improvement to enhance quality, will be provided. This research provides suggestions based on comparisons between complaint cases that occur and benchmark banks. The benchmark bank is a bank that has become the current market leader. It is hoped that, with these suggestions, the company will be able to increase customer satisfaction.